Meta Analysis of Trauma Focused Cognitive Behavior Therapy for Reducing Child Sexual Behaviour in Sexually Abused Children - Andini Damayanti; Ike Herdiana; Ilham Nur Alfian; Rahkman Ardi (Universitas Ahmad Dahlan, 2022)
Child sexual abuse is known to cause adverse effects for its victims, one of them is problem sexual behavior. Problem sexual behavior is sexually oriented behavior done by child aged 12 years or younger and it is developmentally inappropriate or could be harmful for themselves and others. One of the longer term effect is the victim may become sexual offenders if not treated seriously. One of the intervention that can treat problem sexual behavior is Trauma Focused Cognitive Behaviour Therapy or TF-CBT. This review aims to determine the effectivity of TF-CBT. The studies are collected from Science Direct, ProQuest, Sage Journal, Springer Link, Scopus, EBSCO and several repository. The inclusion criteria used are the studies must be RCT, subjects are child victim of sexual abuse who showed problem sexual behavior, the behavior is measured with CSBI (Child Sexual Behavior Inventory) and used TF-CBT as intervention. The result shows that the use of TF-CBT may not be effective for decreasing problem sexual behavior. There are some factors that affect the effectivity of TF-CBT, such as participant’s age, cognition, intensity of trauma and other psychological disorders. However, TF-CBT is potential for decreasing problem sexual behavior because it is directive and uses various behavioral strategies.